Totally green cellulose conversion into bio-oil and cellulose citrate using molten citric acid in an open system: synthesis, characterization and computational investigation of reaction mechanisms. Issue 57 (18th September 2020) - Romeo, Isabella; Olivito, Fabrizio; Tursi, Antonio; Algieri, Vincenzo; Beneduci, Amerigo; Chidichimo, Giuseppe; Maiuolo, Loredana; Sicilia, Emilia; De Nino, Antonio
Abstract : Innovative and efficient conversion of cellulose in furan-based bio-oil and cellulose citrate. Abstract : The simultaneous transformation of crystalline or amorphous cellulose into a furan-based bio-oil and cellulose citrate was realized avoiding the use of strong inorganic acids, drastic conditions, enzymatic treatments or microorganism fermentation. This innovative method is very eco-friendly and involves the use of molten citric acid under solvent free conditions at atmospheric pressure. An accurate discussion on chemical composition of the bio-oil enriched in bioprivileged molecules as well as structural and morphological characterization of cellulose citrate was reported. Moreover, mechanistic hypotheses were formulated on the basis of experimental findings and detailed DFT quantum-mechanical simulations were carried out to confirm, step by step, the proposed reaction paths.